MEWUJUDKAN KESADARAN MASYARAKAT DESA CIPICUNG KP.KUBANG AKAN KEBERSIHAN LINGKUNGAN UNTUK MENGAHADAPI NEW NORMAL - Hasan Basri; Desy Mulyanti; Muhamad Soilihin (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2022)
Health and environmental hygiene are one of the main factors for a healthy, comfortable and clean life. Lack of public awareness of waste that causes problems for the environment such as disruption of public health, floods, water and air pollution and others. This program is not only to improve environmental hygiene and health, but from an environmental point of view, it can produce family health in facing the new era, with the habit of protecting the environment, people will feel health and fight disasters, besides the use of plastic waste that can be used to make handicrafts, both for decoration. as well as household appliances, with this program it is hoped that it can change the mindset of the community towards waste, which at first thought it was trivial to waste. With the efforts of the head of the RT in improving environmental cleanliness and health through this waste program, it also helps the government in achieving clean villages, healthy and comfortable communities. The creation of a healthy, clean, and comfortable environment is not the responsibility of the government alone but the responsibility of all levels of society.